A contingency model of client repatronage in a financial auditing services context - Naruanard Sarapaivanich (2018)
© Emerald Group Publishing Limited. Purpose - This study aims to examine the extent to which switching costs moderates the impact of trust, value and attractiveness of alternatives on client repatronage intentions. Design/methodology/approach - The study combines qualitative and quantitative methodologies to create a cross-sectional survey covering four geographic regions in Thailand. Adopting a contingency perspective, the authors examine the moderating impact of two switching costs (economic and security) on the association among trust, value, attractiveness of alternatives and repatronage intentions. Findings - A study of 519 small- and medium-sized enterprise (SME) clients of audit firms confirms the main effects of trust, value and alternative attractiveness on client retention; some but not all linkages are moderated by the costs of switching. Researchlimitations/implications - This article focuses on one specific segment (SMEs) and one category of professional services. It would be worthwhile to extend the findings to larger firms and other professional services. Originality/value - The study contributes to the understanding of relationship continuance among professional services clients by shifting the focus to when and in which contingency conditions trust, value and attractiveness of alternatives have greater or lesser impacts on repatronage intentions.